Secure FHIR Transactions Based on the SMART on FHIR Approach in a Health Data Exchange...20th World Congress on Medical and Health Informatics (MEDINFO), August 9-13, 2025, Taipei, Taiwan. - RANATUNGE, Rukshan; KARUNAPEMA, Palitha (Studies in Health Technology & Informatics, 2025)
Health data is highly sensitive, and one of the most targeted segments of data in recent cyber-attacks. In the development of the National Electronic Health Record (NEHR), the health data exchanged in FHIR format between electronic medical records and the NEHR had to be secured. A SMART on FHIR standard based authentication tool was developed and implemented in the Ministry of Health data centre in Sri Lanka. The developed solution was released as an open-source tool that can be implemented to secure FHIR based data exchange. The complexity of the SMART on FHIR standard, and the lack of financial and technical capacity poses a long-term challenge to maintain a novel tool for implementation of the standard based authentication to protect FHIR data exchange.